2018
DOI: 10.1111/1462-2920.14082
|View full text |Cite
|
Sign up to set email alerts
|

The pre‐rRNA processing factor Nop53 regulates fungal development and pathogenesis via mediating production of reactive oxygen species

Abstract: Botrytis cinerea is a necrotrophic plant fungal pathogen that annually causes enormous economic losses worldwide. The ribosome is an organelle for cellular protein biosynthesis. However, little is known about how the ribosome operates as a machine to mediate microbial pathogenesis. Here, we demonstrate that Nop53, a late-acting factor for 60S ribosomal subunit maturation, is crucial for the pathogen's development and virulence. BcNop53 is functionally equivalent to yeast nop53p. Complementation of BcNOP53 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 70 publications
0
49
0
Order By: Relevance
“…DAB is converted to dark-brown polymers in the presence of H 2 O 2 and NBT forms a dark-blue water-insoluble formazan precipitate on reduction by superoxide radicals. We also determined the influence of cAMP signalling on conidial germination and/or IFS formation of the tested strains as previously described (Feng et al, 2017;Cao et al, 2018;Hou et al, 2020). Our data demonstrate that the ∆Bccgf1 mutants are difficult to be stained in the germ-tubes and growing mycelia during conidial germination, appressorium, and infection structure formation (Figures 8a and S7); quantification analysis indicated that the relative ROS production by the mutants was significantly reduced (Figure 8b).…”
Section: Loss Of Bccgf1 Impairs Endogenous Ros Production and Camp mentioning
confidence: 68%
See 4 more Smart Citations
“…DAB is converted to dark-brown polymers in the presence of H 2 O 2 and NBT forms a dark-blue water-insoluble formazan precipitate on reduction by superoxide radicals. We also determined the influence of cAMP signalling on conidial germination and/or IFS formation of the tested strains as previously described (Feng et al, 2017;Cao et al, 2018;Hou et al, 2020). Our data demonstrate that the ∆Bccgf1 mutants are difficult to be stained in the germ-tubes and growing mycelia during conidial germination, appressorium, and infection structure formation (Figures 8a and S7); quantification analysis indicated that the relative ROS production by the mutants was significantly reduced (Figure 8b).…”
Section: Loss Of Bccgf1 Impairs Endogenous Ros Production and Camp mentioning
confidence: 68%
“…Two P450 monooxygenase genes (BCIN_07g05430 and BCIN_03g06490) involved in ABA biosynthesis in B. cinerea were upregulated (Table S5). NADPH oxidases are required for ROS production and are involved in conidial germination, differentiation, and vegetative and pathogenicity development as well as virulence in B. cinerea (Marschall and Tudzynski, 2016a;Cao et al, 2018;Hou et al, 2020). NADPH oxidase genes BcNOXA (BCIN_05g00350) and…”
Section: Genes Related To Hormone and Ros Productionmentioning
confidence: 99%
See 3 more Smart Citations